When the Brain Leaves the Scanner and Enters the Clinic: The Role of Neuroscientific Discourses in Producing the Problem of "Addiction". (September 2018) - Barnett, Anthony; Dilkes-Frayne, Ella; Savic, Michael; Carter, Adrian
Addiction neuroscience promises to uncover the neural basis of addiction by mapping changes in the "diseased brains" of people with "drug addictions." It hopes to offer revolutionary treatments for addiction and reduce the stigma experienced by those seeking treatment for a medical, rather than moral, condition. While the promises of addiction neuroscience have received considerable attention, relatively few studies have examined how neuroscientific discourses and promises play out in drug treatment settings. Instead of asking how neuroscience might measure or treat a preexisting addiction "problem, " we draw on poststructuralist ideas to trace how neuroscientific discourses produce addiction as a certain type of "problem" and the effects of these particular problematizations. Based on interviews with a range of different types of treatment providers working in Victoria, Australia, we discuss three themes that reveal neuroscientific discourses at work: (1) constituting pathological subjects, (2) neuroplasticity and "recovery, " and (3) the alleviation of guilt and shame via references to the "diseased brain." On the basis of our analysis, we argue that dominant neuroscientific discourses produce patients as pathologized subjects, requiring medical treatment. We also contend that the intersection of neuroscientific and recovery discourses enacts "recovery" in terms of brain "recovery" through references to neuroplasticity. Further, when neuroscientific and moral discourses intersect, addicted subjects are absolved from the guilt associated with immoral behavior emerging from a "hijacked brain." We conclude by emphasizing the need for future critical work to explore the complex ways in which neuroscientific discourses operate in localized care ecologies.